Crystal structure of 2-bromo-1,3,6,8-tetramethylBOPHY (BOPHY = bis(difluoroboron)-1,2-bis((1H-pyrrol-2-yl)methylene)hydrazine), C14H15B2BrF4N4 - He Weifeng; Liu Yingfan; Sun Saisai; Ji Guangqian; Li Xiaochuan (Zeitschrift für Kristallographie - New Crystal Structures)
C14H15B2BrF4N4, orthorhombic, Pbca (no. 61), a = 11.970(1) Å, b = 10.049(1) Å, c = 27.847(1) Å, V = 3349.6 Å3, Z = 8, R gt(F) = 0.0697, wR ref(F 2) = 0.1585, T = 296 K.